Effects of vitamin E on cigarette smoke induced oxidative damage in larynx and lung - YÜKSEL, MERAL (LIPPINCOTT WILLIAMS & WILKINS, 2006)
Objectives: Cigarette smoke (CS) contains a large variety of compounds, including many oxidants and free radicals (also known as reactive oxygen species), that are capable of initiating or promoting oxidative damage, which leads to various degenerative pulmonary and cardiovascular diseases as well as cancer. Recent studies have established a strong relationship between CS and development of reactive oxygen species (ROS). The aim of the present study was to detect ROS levels in laryngeal and lung tissues of rats by measuring luminol-amplified chemiluminescence and to determine the changes in ROS levels in lung and laryngeal tissues induced by exposure to CS, with and without concurrent treatment with vitamin E. Study Design: Prospective controlled animal study. Methods: Male Sprague-Dawley rats were divided into three groups of eight animals each. The first group of rats was exposed to cigarette smoke. The second group of rats was exposed to cigarette smoke and concurrently treated with vitamin E. The third group was used as control. Animals were killed and chemiluminescence measurements were made for laryngeal and lung tissues. Results: Reactive oxygen species levels were significantly increased in the first group of rats compared to the levels measured in control animals. ROS levels were statistically significantly decreased in the second group as compared to the first group. Conclusion: Our results indicate that vitamin E decreases CS induced ROS levels in laryngeal and lung tissues.
Keywords: LIPID-PEROXIDATION